Strategi Penerapan Manajemen Resiko dalam Rangka Peningkatan Kinerja Instansi Pemerintah di Kota Bekasi - Widodo Indrijantoro; Iwan Irwansyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The Municipal Government of Bekasi has known risk management through elements of risk assessment since 2011, but until now in its implementation it has not yet had an ideal strategy so that the hope of creating good governance has not been fully achieved. As one of the strategic needs in improving organizational performance, risk management is needed in optimizing the use of resources owned by the organization through rearranging the governance system by applying the principles of transparency and accountability. This study aims to determine the factors that have caused the implementation of risk management in the Bekasi City Government to not run effectively and efficiently so that a risk management strategy design is needed that is in accordance with the characteristics of local wisdom in improving the performance of agencies in the Bekasi City Government. The method used in this study is a qualitative case study method with purposive and snowball sampling techniques. As for data collection techniques through in-depth interviews with data processing using triangulation (combined) and is inductive. The final results of this study indicate that risk management must be managed based on the regulation of the Deputy for Supervision of Regional Financial Management No. 04 of 2019 concerning guidelines for risk management in local governments. Performance accountability is the obligation of government agencies to be accountable for their performance achievements, which are set forth in a report through SAKIP. to improve government performance accountability, risks from programs and activities must be managed through good and correct risk management. The implementation of Risk Management is influenced by external factors, namely the OPD within the Bekasi City Government and internally, in this case the Regional Inspectorate Institution; in terms of human resources, budget and other facilities and infrastructure.